Differentiation of Mucilage Secretory Cells of the Arabidopsis Seed Coat - Western, Tamara L. (American Society of Plant Physiologists, 2000)
In some plant species, including Arabidopsis, fertilization induces the epidermal cells of the outer ovule integument to differentiate into a specialized seed coat cell type with a unique morphology and containing large quantities of polysaccharide mucilage (pectin). Such seed coat mucilage cells are necessary for neither viability nor germination under normal laboratory conditions. Thus, the Arabidopsis seed coat offers a unique system with which to use genetics to identify genes controlling cell morphogenesis and complex polysaccharide biosynthesis and secretion. As a first step in the application of this system, we have used microscopy to investigate the structure and differentiation of Arabidopsis seed coat mucilage cells, including cell morphogenesis and the synthesis, secretion, and extrusion of mucilage. During seed coat development in Arabidopsis, the epidermal cells of the outer ovule integument grow and differentiate into cells that produce large quantities of mucilage between the primary cell wall and plasma membrane. Concurrent with mucilage production, the cytoplasm is shaped into a column in the center of the cell. Following mucilage secretion the cytoplasmic column is surrounded by a secondary cell wall to form a structure known as the columella. Thus, differentiation of the seed coat mucilage cells involves a highly regulated series of events including growth, morphogenesis, mucilage biosynthesis and secretion, and secondary cell wall synthesis.